Minimizing buried interfacial defects for efficient inverted perovskite solar cells - Zhang, Shuo; Ye, Fangyuan; Wang, Xiaoyu; Chen, Rui; Zhang, Huidong; Zhan, Liqing; Jiang, Xianyuan; Li, Yawen; Ji, Xiaoyu; Liu, Shuaijun; Yu, Miaojie; Yu, Furong; et al. (Science (American Association for the Advancement of Science), 2023)
Controlling the perovskite morphology and defects at the buried perovskite-substrate interface is challenging for inverted perovskite solar cells. In this work, we report an amphiphilic molecular hole transporter, (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphonic acid, that features a multifunctional cyanovinyl phosphonic acid group and forms a superwetting underlayer for perovskite deposition, which enables high-quality perovskite films with minimized defects at the buried interface. The resulting perovskite film has a photoluminescence quantum yield of 17% and a Shockley-Read-Hall lifetime of nearly 7 microseconds and achieved a certified power conversion efficiency (PCE) of 25.4% with an open-circuit voltage of 1.21 volts and a fill factor of 84.7%. In addition, 1–square centimeter cells and 10–square centimeter minimodules show PCEs of 23.4 and 22.0%, respectively. Encapsulated modules exhibited high stability under both operational and damp heat test conditions. Many of the hole-transport materials used in inverted perovskite solar cells are either too hydrophobic to wet perovskite precursors or can react with the perovskite, which causes the buried interface between these layers to develop performance-limiting defects. Zhang et al . report that an amphiphilic molecular hole transporter with a hydrophilic cyanovinyl phosphonic acid (CPA)–anchoring group and a hydrophobic arylamine–based hole-extraction group (MPA-CPA) minimized the buried interfacial defects by enhancing perovskite deposition through wetting and passivation. The perovskite films had high uniformity, high photoluminescence quantum yield, and long carrier lifetimes. Encapsulated 1-square-centimeter solar cells had a power conversion efficiency of 23.4% and high operational and damp heat test stability. —Phil Szuromi The buried interface of inverted perovskite solar cells is improved by using an amphiphilic molecular hole transporter.